2012
DOI: 10.1056/nejmoa1108524
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Prophylaxis for HIV Prevention in Heterosexual Men and Women

Abstract: Introduction Antiretroviral pre-exposure prophylaxis (PrEP) reduces the incidence of acquisition of human immunodeficiency virus type 1 (HIV-1) in men who have sex with men and is a promising approach for preventing HIV-1 in heterosexual populations. Methods We conducted a randomized, three-arm trial of oral antiretroviral PrEP among heterosexual couples from Kenya and Uganda in which one member was HIV-1 seronegative and the other HIV-1 seropositive. Seronegative partners were randomly assigned to once-dail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
2,542
3
24

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 2,817 publications
(2,600 citation statements)
references
References 36 publications
31
2,542
3
24
Order By: Relevance
“…The protection that was observed in this trial among high-risk women is lower than that shown with once-daily tenofovir or combination tenofovir-emtricitabine oral prophylaxis in men who have sex with men 19 and in heterosexual HIV-1-discordant couples. 20 However, in two clinical trials of tenofovir and of tenofovir or tenofovir-emtricitabine oral prophylaxis in participants who are similar to those enrolled in our trial, no protection against HIV-1 infection was observed, because of poor adherence to the daily use of the trial drugs. 11,12 Similarly, in studies that evaluated microbicides, one study of a vaginal gel containing tenofovir showed evidence of protection from HIV-1 infection, 21 but this result was not confirmed in subsequent studies.…”
Section: Discussionmentioning
confidence: 54%
“…The protection that was observed in this trial among high-risk women is lower than that shown with once-daily tenofovir or combination tenofovir-emtricitabine oral prophylaxis in men who have sex with men 19 and in heterosexual HIV-1-discordant couples. 20 However, in two clinical trials of tenofovir and of tenofovir or tenofovir-emtricitabine oral prophylaxis in participants who are similar to those enrolled in our trial, no protection against HIV-1 infection was observed, because of poor adherence to the daily use of the trial drugs. 11,12 Similarly, in studies that evaluated microbicides, one study of a vaginal gel containing tenofovir showed evidence of protection from HIV-1 infection, 21 but this result was not confirmed in subsequent studies.…”
Section: Discussionmentioning
confidence: 54%
“…More than 30 years into the HIV/AIDS epidemic, an effective HIV vaccine remains an elusive public health goal. Despite important discoveries about the effectiveness of prevention interventions, such as male circumcision 32,33 and the use of antiretroviral drugs such as microbicides, 34 prophylactic therapy for HIV-uninfected individuals, 35,36 or life-long suppressive therapy for infected individuals, 37 an effective vaccine able to confer long-term immunity is still considered a necessity if we are to eventually end the global AIDS pandemic. 38 Our objectives with this research were to investigate (1) whether trust in research and HIV conspiracy beliefs differed by racial/ ethnic group among community-recruited individuals in a large metropolitan area in the Midwest, and (2) whether trust in research and HIV conspiracy beliefs were associated with willingness to participate in HIV vaccine trials.…”
Section: Introductionmentioning
confidence: 99%
“…A more comprehensive review that included treatmentbased HIV prevention interventions would certainly be valuable because over the past few years several largescale studies have appeared supporting the usefulness of these interventions and some analysts now believe that successful efforts to reduce the incidence of HIV in the US must include a treatment-based HIV prevention initiative [8][9][10][11][12]. A recent CDC publication states that, ''Now that early ART of HIV-infected persons has been shown to be very effective at preventing secondary transmission of HIV among individuals, the current goal is to determine the extent to which ART can be used broadly and effectively to reduce the spread of HIV within a population [13]''.…”
Section: Treatment-based Hiv Preventionmentioning
confidence: 99%